Panic-related hyperventilation resulting in hypophosphataemia and a high lactate. (9th May 2013) - Suarez, Nicolas; Conway, Nerys; Pickett, Tom
Abstract : A 22-year-old lady presented to the emergency department with dyspnoea and pleuritic chest pain. Life-threatening asthma, pulmonary embolus and pneumothorax were all excluded. However, investigations did show an unexplained hypophosphataemia and raised lactate, both of which were subsequently attributed to hyperventilation with a component of panic. Here we explore the mechanism of these findings and the management of hypophosphataemia.